Yodel king of hindi films : kishore kumar - Basil Hans V (Ghaziabad P&P Academy, 2025)
Yodel King of Hindi Films: Kishore Kumar is an exploration of his life and legacy. It seeks to uncover not only the milestones of his prolific career but also the moments of struggle, satire, spontaneity, and solitude that defined his journey. From his early days in Khandwa to the peak of his superstardom in Mumbai, from comic brilliance on screen to hauntingly beautiful ballads behind the mic-this book delves into the man behind the magic.ecdotes, sharp insights, and heartfelt tributes, this is a celebration of an artist whose genius still echoes across generations.
Keywords: Motion Pictures